A strong solution for a generalized plane strain unsymmetrical piezoelectric bi-layer laminates. Issue 2 (25th January 2017) - Wu, Z. J.; Han, C.
ABSTRACT: Interfacial stresses, electric fields, and electric displacements of a piezoelectric unsymmetrical bi-layer orthotropic laminate are presented. A state space equation for orthotropic piezoelectric material is derived from three-dimensional piezoelectric elasticity directly. With the application of the transfer matrix and recursive solution approach, a strong solution for the unsymmetrical piezoelectric generalized plane strain bi-layer laminated structure is sought after considering all elastic and piezoelectric constants of materials. Electromechanical boundary layer effect is identified quantitatively at free edges. To facilitate the discussion on the results, the corresponding calculations from finite element models are compared with those of the strong solution.